One-stage hybrid procedure without sternotomy for treating thoracic aortic pathologies that involve distal aortic arch: a single-center preliminary study - Ren, Changwei (J Thorac Dis, 2015)
OBJECTIVE: This study aims to evaluate the initial results of a hybrid procedure without sternotomy for treating descending thoracic aortic disease that involves distal aortic arch. It also intends to report our initial experience in performing this procedure. METHODS: A total of 45 patients (35 males and 10 females) with descending thoracic aortic disease underwent a hybrid procedure, namely, thoracic endovascular aortic repair (TEVAR) combined with supra-arch branch vessel bypass, in our center from April 2009 to August 2014. Right axillary artery to left axillary artery bypass (n=20) or right axillary artery to left common carotid artery (LCCA) and left axillary artery bypass (n=25) were performed. The conditions of all patients were followed up from the 2(nd) month to the 65(th) month postoperative (mean, 26.0±17.1). Mortality within 30 days, complications such as endoleak after the hybrid procedure, and stenosis or blockage of the bypass graft during the follow-up period was assessed. RESULTS: All the patients underwent a one-stage procedure. One case of death and one case of cerebral infarction were reported within 30 days. One patient died of the sudden drop in blood pressure during the 2(nd) day of operation. Meanwhile, another patient suffered from cerebral infarction. Two patients underwent open surgery, and one of them had to undergo a second TEVAR during the follow-up period. Moreover, endoleak occurred in two patients and a newly formed intimal tear was observed in one patient. Overall, 93.2% of the patients survived without any complication related to the hybrid procedure. CONCLUSIONS: Initial results suggest that the one-stage hybrid procedure is a suitable therapeutic option for thoracic aortic pathologies that involve distal aortic arch. However, this procedure is not recommended for type-B aortic dissection, in which a tear is located in the greater curvature or near the left subclavian artery (LSA), because of the high possibility of endoleak occurrence.